2018
DOI: 10.3390/ijerph15020321
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Baduanjin Exercise for Depression and Anxiety in People with Physical or Mental Illnesses: A Systematic Review and Meta-Analysis

Abstract: Objectives: we used a quantitative method to systematically synthesize the emerging literature and critically evaluate the effects of Baduanjin on depression and anxiety in people with physical or mental illnesses. Additionally, we determined if the number of total Baduanjin training sessions is associated with decreased anxiety and depression levels. Methods: both English and Chinese databases were searched for potential studies published between January 1982 and October 2017. The eligible randomized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 32 publications
(35 reference statements)
8
84
0
1
Order By: Relevance
“…Signi cant individual reductions of mood symptoms after completion in both the MBCT and HQCT groups were indicated. Our ndings were consistent with previous research on the bene cial impacts of MM and HQ on depression and anxiety [11,17]. Previous research only showed small-to-moderate e cacy for reducing mood symptoms [42] or without reliably effects being shown at follow-up assessments [10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Signi cant individual reductions of mood symptoms after completion in both the MBCT and HQCT groups were indicated. Our ndings were consistent with previous research on the bene cial impacts of MM and HQ on depression and anxiety [11,17]. Previous research only showed small-to-moderate e cacy for reducing mood symptoms [42] or without reliably effects being shown at follow-up assessments [10].…”
Section: Discussionsupporting
confidence: 91%
“…HQ can be viewed as a kind of physical movement with introspective focus of breathing and energy in the body [15]. HQ should be able to reduce depression or anxiety in people with physical or mental illness [16,17]. The combination of HQ with CBT could be considered as one of the major behavioral strategies in countering mood symptoms [18].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, BD with mild exercise intensity has recently received substantial attentions from the research community. As the number of trials increase, researchers subsequently conducted several systematic reviews with meta-analytic method, suggesting that BD has therapeutic effects for individuals with medical conditions (depression, anxiety, insomnia, chronic obstructive pulmonary disease, musculoskeletal pain, and stroke) (27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…As a mind-body exercise, Baduanjin postures can strengthen muscles [16], coupled with breathing regulation and a relaxed state of mind [18], it may help individuals decrease pain sensitivity and change the perception of it. Evidence have demonstrated that Baduanjin training increases the excitation of the middle cerebral cortex, helps to down-regulate anxiety and negative emotions [34], and promotes mental health [35]. In a state of peace of mind, individuals are more likely to make positive and correct decisions in self-management [36], and the impact of discomfort such as pain on the body may also be reduced [37].…”
Section: Discussionmentioning
confidence: 99%